STUDI EKSPERIMENTAL PENGGUNAAN BOSS CAP FINS UNTUK MENINGKATKAN EFISIENSI PADA PROPELLER - Budi Rolly Yuana; Siti Sadiah; Kristian Hadi Siswanto; Setyo Leksono (Universitas Lambung Mangkurat, 2018)
The phenomena of cavitation which occurs when the propeller work can cause adverseeffects. One of them is the ship would miss the thrust so that the speed can not beachieved as expected. Various experiments and researches have been done in an effort toobtain maximum results by reducing or even eliminating cavitation occurring.One of these efforts is to reduce or eliminate cavitation occurring on the hub vortex. Thisis done by modifying the propeller without changing the original design self. Thepropeller boss cap is modified by adding fins / fin, and then examines the differencesbetween the cavitation that occur with a standard cap boss the modified. It is thencalculated how big the impact on the efficiency of the propeller. In this study, propellermodels of type B series 4:45 (model no. 3468) is used. The test conducted in thecavitation tunnel Laboratory for Hydrodynamics, BPP Technology in Surabaya.From the results of efficiency measurements and observations conducted cavitation it wasfound that modifications made to be able to eliminate the hub vortex cavitation therebyincreasing the efficiency up to 8.58%.